2022
DOI: 10.31219/osf.io/yn6tc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate anxiety, pro-environmental action and wellbeing: antecedents and outcomes of negative emotional responses to climate change in 28 countries

Abstract: This study explored the antecedents and outcomes of negative emotional responses to climate change among people from a diverse range of cultural and national contexts. We analysed cross-sectional data gathered in 28 countries (N = 10,963). Our results show that negative emotional responses to climate change are positively related to the amount of attention people pay to climate change information, rates of exposure to information about climate change impacts, and perceived social expectations regarding emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… 31 Climate distress was previously found to be strongly and positively correlated with self-efficacy and responsibility—the two metrics we compiled to form our agency scale 31 —and observations available in Feb, 2022 (preprint) from young people in 28 countries suggest that engagement with climate issues and negative beliefs about the global future might be related to both climate distress and higher self-efficacy. 48 On the other hand, a 2020 study in US adults found that climate anxiety was not correlated with behavioural engagement. 30 Further research is needed to explore the potentially non-linear relationship between emotional and behavioural engagement with climate change.…”
Section: Discussionmentioning
confidence: 98%
“… 31 Climate distress was previously found to be strongly and positively correlated with self-efficacy and responsibility—the two metrics we compiled to form our agency scale 31 —and observations available in Feb, 2022 (preprint) from young people in 28 countries suggest that engagement with climate issues and negative beliefs about the global future might be related to both climate distress and higher self-efficacy. 48 On the other hand, a 2020 study in US adults found that climate anxiety was not correlated with behavioural engagement. 30 Further research is needed to explore the potentially non-linear relationship between emotional and behavioural engagement with climate change.…”
Section: Discussionmentioning
confidence: 98%
“…To further probe the CCD-PEB association, future work should attempt to experimentally induce different statelevels of CCD and measure subsequent PEB levels. Additionally, future work should consider manipulating features of PEB such as the level of effort required and personal cost associated with the behavior to better understand in which contexts CCD and CCI predict PEB 61,62 .…”
Section: Validitymentioning
confidence: 99%